Potts model solver based on hybrid physical and digital architecture - Kensuke Inaba; Takahiro Inagaki; Koji Igarashi; Shoko Utsunomiya; Toshimori Honjo; Takuya Ikuta; Koji Enbutsu; Takeshi Umeki; Ryoichi Kasahara; Kyo Inoue; Yoshihisa Yamamoto; Hiroki Takesue (Communications Physics, 2022)
Hybrid computing seeks to divide operations based on the strengths of digital, analogue or physical architectures. Here, approximate solutions to the multi-state Potts model are found using a physical Ising solver, networked degenerate optical parametric oscillators, repeatedly with learning processes.